Content Analysis of Master’s and PhD Thesis on Climate: Studies Conducted in The Field of Education in Türkiye - DEMİRBAŞ, İbrahim (Bilgicagi Education Consulting and Publishing Industry Trade Limited Company, 2023)
Through geography education, students make connections between natural phenomena, environment and behavior, and climate and climate change. Climate Science is positioned as “a sub-branch of geography classified under physical geography as a basic field of study”. Climate; It is expressed as the average condition of weather conditions such as precipitation, temperature, pressure, humidity and wind as a result of long-term observations in a place. When the literature is examined, there are many studies on climate in the field of education. These studies differ in terms of research topic, method and sample. It has been determined that there are no studies aimed at determining the direction of master’s and doctoral theses on climate in the field of education. The aim of our research is to reveal the current situation by evaluating the content of master’s and doctoral theses on climate in the field of education. Document review method was used in the research. The data were analyzed through content analysis. As documents, 73 studies, including master’s and doctoral theses on climate in the field of education in our country, were examined. According to the results obtained, it is seen that the postgraduate studies on climate in the field of education are predominantly on master’s thesis and the majority of the studies were conducted in 2022. In addition, it was seen that most of the climate theses were made at Gazi University. In the studies, climate change and global warming were mostly discussed, and it was determined that the method used was mostly descriptive scanning method. In the studies, the preferred sample group was students.
Keywords: Sosyal Bilgiler Eğitimi; Social Studies Education; Geography Education; Coğrafya Eğitimi; Education; master’s thesis; doctoral thesis; climate; content analysis; 13. Climate action; 4. Education